Relevansi Kitab Khulāṣah dalam Pendidikan Karakter: Sebuah Tinjauan pada Materi Sejarah Kebudayaan Islam - Asmanah; Mahrus, Erwin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
The story of the life journey of the Prophet Muhammad in the book Khulāṣah Sīrah al-Muḥammadiyah, translated by Maharaja Imam Sambas, H. Muhammad Basiuni Imran is very inspiring and full of examples. This work also provides new nuances for the advancement of the field of education in general, and the field of character education, in particular. The characteristics of the Prophet such as honesty, trustworthiness, responsibility, patience, social care, peace-loving, forgiving, religious, fair, and having a very, very good leadership spirit can be a minimum benchmark for students' character graduation in pursuing education. Through this article, the researchers explain the relevance of the material in the Islamic Cultural History (SKI) subject with the Khulāṣah book as the main aim of the research. This research uses two methods, namely literature and textology. The results and conclusions of this research are that the material in the Islamic Cultural History (SKI) subject used at the Madrasah Tsanawiyah level is 75% relevant to the Khulāṣah book.